Kuhn e a noção de 'Exemplar' - Abrantes, Paulo Cesar Coelho (1998)
In thts paper I argue that Kuhn's analysts of the role played by `exemplars' in normal sctence should be considered one of hts most important contrtbuttons to the Philosophy of Sctence The paper makes a detailed analysts of the relattonship between the various elements of a 'clisciplinary matrix)— emptrzcal generalizations, models and exemplars — starting with Kuhn's views as exposed in vartous of kis books and papers Kuhn's analysts is znvestigated in the context of the discussions, In the 50s and 60s, about the notion of `model' In the so called `recetved vtew' of the structure of scienttfic theortes I refer also to the atues of logical empincism at this time, that were concerned with analogtcal models and tnspired by Campbell's studies on the dynamics of theortes I argue also that Polanyt's notton of 'ateu knowledge' and some of kis discussions of the role played by analogies tn mathematics have been an Important influence on Kuhn The paper tndicates, furthermore, how Kuhn's intuttions concerntng exemplars are being developped in the present, by plulosophers of sc-tence like Thagard, Paul Churchland and Gzere, that adopt a `cognitivise stance towards scientific reasontng.